The Lumbee Indians : An American Struggle - Lowery, Malinda Maynor; Project Muse. (Chapel Hill : The University of North Carolina Press, 2018)
"As the largest tribe east of the Mississippi and the ninth largest in the country, the Lumbees have survived in their original homelands, maintaining a distinct identity as Indians in a bi-racial South. In a work both concise and expansive, Lumbee historian Malinda Maynor Lowery tells this story of survival with a breakthrough approach to rigorous scholarship and personal storytelling. The Lumbees' journey sheds new light on America's defining moments, from the first encounters with Europeans to the present day. How and why did the Lumbees fight to establish and resist the United States? How have they not just survived, but thrived, through Civil War, Jim Crow, the Civil Rights movement, and the War on Drugs, to ultimately establish their own constitutional government in the twenty-first century? Their fight for full federal acknowledgement continues to this day, while the Lumbee people's struggle for justice and determination continues to transform our view of the American experience"--
5. Integration or Disintegration: Civil Rights and Red PowerInterlude: Journeys, 1972-1988; 6. They Can Kill Me, but They Can't Eat Me: The Drug War; Interlude: Cherokee Chapel Holiness Methodist Church, Wakulla, North Carolina, January 2010; 7. A Creative State, Not a Welfare State: Creating a Constitution; EPILOGUE; ACKNOWLEDGMENTS; NOTES; INDEX; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z
Description based on print version record.
Keywords: Lumbee Indians; Indians of North America; HISTORY -- Native American; HISTORY -- United States -- State & Local -- South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); Indiens d'Amerique -- Caroline du Nord; Lumbee (Indiens) -- Caroline du Nord -- Histoire; Indians of North America -- North Carolina; Lumbee Indians -- North Carolina -- History; North Carolina; Lumbee Tribe of North Carolina; Lumbee Tribe of North Carolina; History; Electronic books